Fintech and financial inclusion in the digital era: The impact on the reduction of poverty and informality in Peru - Vargas García, Allan (2019)
Financial inclusion means having access to services that solve a problem or satisfy a financial need of the population in order to reduce informality and poverty. These financial services are operations of capital transfers, purchase- sale of currencies, payments of services, loans, savings, insurance, etc. According to Scottish Executive (2005) Financial Inclusion is “Access for individuals to appropriate financial products and services. This includes people who have the skills, knowledge and understanding to make the best use of those products and services. Financial exclusion is often a symptom of poverty, as well as a cause”. The access to financial services contribute to create business opportunities for the population, generating sustainable income in the long term with the objective of a better standard of living. Financial technology is an important tool to achieve these ends, since it allows easy access to perform transactions at low cost and according to the needs of users. In line with the above, fintech startups have gained great importance in recent years, since they have taken as a business line some of the main activities carried out by a financial institution offering services quickly, highly specialized and at low cost. In Peru (2017), there are high levels of poverty 22% and informality of GDP 18% and according to studies carried out by multilateral organizations to decrease these indicators we can use technology; however, in the field of technological development we occupy the last places in the world, according to the ranking of Institute for Management Development 2018.